2002
DOI: 10.1023/a:1020807613155
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two variants of a behavioral family intervention (BFI) program known as Triple P were compared using 87 preschoolers with co-occurring disruptive behavior and attentional/hyperactive difficulties. Families were randomly allocated to enhanced BFI (EBFI), standard BFI (SBFI), or a waitlist (WL) control group. At postintervention both BFI programs were associated with significantly lower levels of parent-reported child behavior problems, lower levels of dysfunctional parenting, and greater parental competence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
62
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(83 citation statements)
references
References 26 publications
7
62
1
8
Order By: Relevance
“…A second study by the same team of investigators evaluated the same standard and enhanced BPT programs as employed with 87 preschoolers (3 years of age) with co-occurring disruptive behavior and attentional/hyperactivity difficulties (Bor et al 2002). In this study, the enhanced CBPT program was not superior to the standard BPT at either post-intervention or follow-up based on parent report or observations (see Table 1).…”
Section: Cognitive Enhancements Within Bpt: Effects On Treatment Outcomementioning
confidence: 93%
See 1 more Smart Citation
“…A second study by the same team of investigators evaluated the same standard and enhanced BPT programs as employed with 87 preschoolers (3 years of age) with co-occurring disruptive behavior and attentional/hyperactivity difficulties (Bor et al 2002). In this study, the enhanced CBPT program was not superior to the standard BPT at either post-intervention or follow-up based on parent report or observations (see Table 1).…”
Section: Cognitive Enhancements Within Bpt: Effects On Treatment Outcomementioning
confidence: 93%
“…Level five of Sander's well-known Triple P--Positive Parenting Program includes an adjunctive intervention (CBPT) that addresses parent mood management strategies, stress coping skills, and marital partner support skills, in addition to the standard BPT program (Bor et al 2002;. conducted an intervention trial among 305 families with a 3-year-old child at high risk of developing conduct problems, who were randomly assigned to one of four conditions: standard BPT, enhanced CBPT (i.e., Level 5 of Triple P), self-directed BPT, and wait-list control.…”
Section: Cognitive Enhancements Within Bpt: Effects On Treatment Outcomementioning
confidence: 99%
“…Empirical evidence suggests that early intervention is an important component in preventing later negative developmental consequences. Therefore, the development of efficacious interventions which involve parents is essential for long-term benefit on the well-being and quality of life of young children with challenging behaviors and their families (Bor et al, 2002;Dupaul et al, 2002;Kazdin, 1997;Sanders et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies attest that achieving positive treatment outcomes for young children is enhanced when interventions implemented by parents as the primary intervention agents. Interventions should also be embed into the natural environment during the daily routines that the family has identified as problematic (Bor et al, 2002;Cripe and Venn, 1997;Hancock et al, 2002;Horner et al, 2000;Kashinath et al, 2006;Lucyshyn et al, 2007;Pfiffner et al, 2007;Rocha et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An integrated series of controlled outcome studies has provided considerable evidence demonstrating the benefits of the various levels of intervention and modes of delivery in a variety of populations (see Sanders 2008). This program of research has shown successful outcomes with a number of populations and problem areas, with consistent improvement in quality of parenting across studies (e.g., Bor et al 2002;Sanders and McFarland 2000). Triple P has been evaluated as a universal, whole of population strategy and shown to strengthen parenting and reduce the prevalence of conduct problems in preschool-aged children from high-risk neighborhoods (Zubrick et al 2005), and to reduce coercive parenting practices through the implementation of multiple levels of Triple P .…”
mentioning
confidence: 99%